Myocardial function after off-pump coronary artery bypass grafting with combined epidural and inhalation anesthesia - K. V. Paromov; D. A. Volkov; N. V. Nizovtsev; M. Yu. Kirov (Вестник анестезиологии и реаниматологии)
There are certain debates regarding epidural anesthesia (EA) and analgesia in cardiac surgery.The objective: to evaluate functions of left ventricle (LV) and right ventricle (RV) function with echocardiography after off-pump coronary artery bypass grafting (OPCAB) using combined inhalation and epidural anesthesia.Subjects and methods: 68 patients were randomized into 2 groups, differed by anesthesia techniques. In Group 1 (GA, n = 34), we used general anesthesia with sevoflurane and fentanyl, while in Group 2 (CA, n = 34) – its combination with epidural anesthesia by 0.5% ropivacaine followed by infusion of 0.2% ropivacaine after OPCAB. Parameters of cardiac performance and ventricular function were assessed by echocardiography.Results. There were no differences in systolic function of LV, RV, diastolic function of LV between the groups. The difference in the left atrial strain was revealed before hospital discharge and made 18.0 (14.5‒21.5) % in CA Group and 24.0 (18.0–26.0)% in GA Group (p = 0.028).Conclusions. The use of epidural anesthesia and analgesia is not associated with clinically significant changes in inotropic and lusitropic functions of LV as well as RV systolic function after OPCAB.